Leadership capabilities in Fiji$1 (Bs civil service: perspectives of senior officialss - Andrews, Kelvin (2019)
This article addresses views on leadership capabilities in Fiji$1 (Bs civil service and the lessons for their ongoing development. The discussion is based on a survey of the capability perspectives of officials who comprise the service$1 (Bs leadership cadre. Of particular interest are capabilities highlighted in a well-respected leadership capability framework. A significant finding is that permanent secretaries of ministries rated the capabilities of their leadership teams lower than other respondents did. Further research could valuably be conducted into the nature and significance of the service$1 (Bs leadership capability and development needs. - Reproduced.s
Keywords: Leadership